THE APPROACH OF IBN TABATIBA AL-ASBAHANI TO THE ISSUE OF WORD AND MEANING CASTING AND THE PROBLEMATIC ARTISTIC IMAGERY - Ad-dakhil, Mohammad Majid (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2014)
This study shows that intends to address the issue of "word-meaning" as addressed in work "iyar al syi’r", in addition to the issue of poetical discourse, effects on the poetical imagination of a creative poet, and aesthetical brightening of an artistic poetical imagery. This study also shows that Ibn Tabatiba in his work "Eyar Ash shir" took the pretense (sana'a) as a basis on which based his judgmental criticism appraisals, giving priority to form rather than content, finally the study shows that while recognizing the importance of the later.